Geometric morphometric analysis of malocclusion on lateral cephalograms in Malaysian population - Choy Ker Woon; Nurul Aiman Abu Jamal; Muhamad Nasim Ilmi Mohd Noor; Syiral Mastura Abdullah; Nurjehan Binti Mohamed Ibrahim; Noraina Hafizan Norman; Aspalilah Alias (Medrang, 2024)
Indexed by WOS/Scopus